2018
DOI: 10.3311/pptr.12107
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Different Strength Steels MIG Brazed Joints

Abstract: Nowadays the stakeholders of vehicle industry are focusing on making materials and technologies for motor-vehicle bodies that satisfy the newest requirements. Reduction of the manufactured vehicle's dead load – while the important material properties of proper functioning only change in a small degree – is such a requirement. There exist many solutions to satisfy this requirement. One of them is when the materials are in the same group, but the material with higher strength is used with less thickness. Reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Berczeli et al studied the mechanical behavior of dissimilar welds between a zinc-coated DP 600 steel and DC 01 steel, with a CuSi 3 electrode. The authors found that there is a maximum in the hardness profile at the edge of the DP-600 steel and the CuSi 3 welding material [12]. Singh et al evaluated the CMT welding process for lap joining of zinc-coated DP-780 steel with a CuAl 10 Fe filler wire and observed that the heat input increased the concentration of intermetallic compounds from 13.9% to 15.6% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Berczeli et al studied the mechanical behavior of dissimilar welds between a zinc-coated DP 600 steel and DC 01 steel, with a CuSi 3 electrode. The authors found that there is a maximum in the hardness profile at the edge of the DP-600 steel and the CuSi 3 welding material [12]. Singh et al evaluated the CMT welding process for lap joining of zinc-coated DP-780 steel with a CuAl 10 Fe filler wire and observed that the heat input increased the concentration of intermetallic compounds from 13.9% to 15.6% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Non‐locality (in space) appears in a generalized fractional strain. Instability problems are often coupled with spontaneous crack formation . Such problems are successfully treated by using fractional stress derivative in peridynamics .…”
Section: Introductionmentioning
confidence: 99%